Violence in Couple Relationships: Relational Factors, Family of Origin Experiences and Coping Strategies - Suat Kılıçarslan; İzzet Parmaksız (Anı Publishing, 2020)
Violence in couple relationships, both in Turkey and in the world, is amongst the major problems. There is a need for different studies revealing what affects the relationships between couples and how they are affected, how the relationships in the family origin of individuals are reflected on the relationships between couples and how to deal with this problem between couples. In this context, in this study, the causes of violence in couple relationships, strategies of coping with violence in the couple's relationship, and the effects of the origin family experiences of the couple on the couple relationship, unlike other studies in the literature, were examined. This study is a descriptive study and phenomenology, a qualitative research type, was used as the research design. The research data were obtained through semi-structured interviews, which are qualitative research methods. Content analysis method was used to analyze the data. As a result of the research, it has been revealed that the violence experienced by married individuals in couple relationships reflects not only individual characteristics of individuals but also the relational experiences of couples and intergenerational family interaction.